Low quality of dying and death in patients with septic shock as perceived by nurses and resident physicians. Issue 8 (13th September 2016) - Van Scoy, Lauren Jodi; Reading, Jean M.; Howrylak, Judie A.; Tamhane, Apurva; Sherman, Michael S.
ABSTRACT: Septic shock is a disease with both high prevalence and mortality. Few studies have evaluated the quality of dying and death (QODD) in patients with septic shock. The authors compared the QODD of patients who died of septic shock versus other causes. They prospectively collected QODD surveys from nurses and residents caring for 196 patients who died in the medical intensive care unit (ICU) at an urban, university hospital. Patients were included in the analysis if either a nurse or resident returned a survey. Chart review established cause of death. The authors compared total QODD scores (on a scale of 0–100) and a single-item score (QODD-1; on a scale of 0–10) of patients who died of septic shock versus other causes. Survey response rates were 59% ( n = 155) for residents and 49% ( n = 129) for nurses. Nurses rated patients as having lower total QODD and QODD-1 scores for septic (Δ 7.5 points, p = 0.03, and 0.9 points, p = 0.05, respectively). Residents rated septic patients with lower QODD-1 scores than nonseptic patients (Δ 0.8 points, p = 0.03). This study shows that nurses rate patients with septic shock as having lower QODD than patients dying of other causes. These findings are important for clinicians who counsel families of patients dying of septic shock.